Profile of visitors of Alta and Patrocínio Amaro waterfalls, Ipoema district, Itabira (MG), as a subsidy for tourism development on sustainable bases (Research, Society and Development, 2018)
Tourism is an activity that causes the displacement of those people who look for their well-being, especially for spaces that have a high environmental value. In this sense, the district of Ipoema, Itabira (MG) has natural attractions that draw tourists to the region. In this way, this work aimed at analyzing the tourists profile that go into Alta and Patrocínio Amaro waterfalls, located in this locality. The data for this research were obtained through a questionnaire, applied to 63 tourists who visited these natural attractions between June and August 2016. It was observed that the tourists were mostly from the metropolitan area of Belo Horizonte (MG), with over 25 years of age and complete upper level of schooling. It should also be noted that a significant number of tourists indicated that the fees charged for access to tourist attractions should be used to preserve the sites, being generally satisfied with the environments offered. However, despite the level of schooling observed, it is common the presence of solid waste left by tourists in the attractions, highlighting the need to adopt Environmental Education practices involving visitors.